Matriptase-2, a Regulatory Protease of Iron Homeostasis: Possible Substrates, Cleavage Sites and Inhibitors - Stirnberg, Marit; Gutschow, Michael (Current Pharmaceutical Design, 2013)
Matriptase-2 is a cell surface serine protease with a modular structure. The exploration of its function in iron homeostasis was of significance for the understanding of the regulation of hepcidin expression, the master protein in iron control. Mutations in matriptase- 2 cause iron-refractory iron deficiency anemia (IRIDA), an iron deficiency disorder where the level of hepcidin is inappropriately high. Matriptase-2 controls hepcidin expression through the suppression of bone morphogenetic protein (BMP)/sons of mothers against decapentaplegic homologue protein (SMAD) signaling, probably by cleaving the BMP co-receptor hemojuvelin. Since prospective studies revealed that genetic inactivation of matriptase-2 reduces iron loading in different mouse models, matriptase-2 becomes highly attractive as a novel target for the design of low-molecular weight inhibitors. The first synthetic peptidomimetic matriptase-2 inhibitors have been reported. A computational model of the active site of matriptase-2 based on the X-ray crystal structure of the close homologue matriptase was generated and mutational studies were performed in order to identify critical amino acids specifying the preferred recognition site of matriptase-2. So far, the only known putative natural substrates of matriptase-2 are hemojuvelin and matriptase-2 itself, as this protease undergoes complex auto-processing during zymogen activation. Cleavage sites within both natural substrates were identified.
Keywords: type II transmembrane serine protease